Investigasi Logistics Service Quality Terhadap Loyalitas Pengguna Jasa Ekspedisi - Yelita Anggiane Iskandar; Sarah Nur Azizah; Gita Kurnia (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Purpose – This study aims to analyze the factors that influence customer loyalty in using AS Express package services.Methodology – The sampling technique used a nonprobability sampling technique with a purposive sampling method with a sample size of 143 respondents, while data analysis was carried out using the PLS-SEM method.Findings – The results of the study indicate that customer satisfaction is the most influential factor on customer loyalty while the variables customer expectations, customer satisfaction, and attitude can indirectly affect customer loyalty. Then it was also obtained that only subjective norms have a significant positive effect on customer loyalty with path coefficient, t-statistics, and p-value values of 0.300; 3.499; and 0.000, respectively.Originality/Novelty – The novelty of this paper is logistics service quality and its effect on the loyalty of expedition service users, as well as the incorporation and modification of the use of the Theory of Planned Behavior and the American Customer Satisfaction Index model on several variables that make it up.Implications – Implications for AS Express, it is necessary to know customer expectations so that customers are not disappointed and feel satisfied after using AS Express services. In addition, AS Express can conduct benchmarking with competitors so that AS Express can improve its performance by making improvements from the results of the evaluation. Benchmarking can help AS Express understand customer expectations, increase customer satisfaction and loyalty, and be one way to increase shipping transactions so that the company's profitability also increases.